The myth of Prester John: early European imaginings of the Orient - Ramos, M. J. (Traveller’s Eye: Selected works from the Francisco Capelo Asian collections, 2019)
What strange reason led ancient Abyssinia to be identified by European cosmographers of the late Middle Ages, and later contacted by Portuguese navigators at the beginning of the 16th century, as the “kingdom of Prester John of the Indies”? Abyssinia was the name by which the Christian kingdom that for many centuries dominated the highlands of the north of Ethiopia was known. Medieval European geographical conceptions, influenced by Aristotelian physics, conceived that the oecumena (the non-submerged and habitable part of the terrestrial sphere) had a generically circular shape and was divided into three great regions, Asia, Europe and Africa. The last two were separated by the Mediterranean Sea, and Asia was the whole territory stretching eastward beyond two great rivers: the Danube and the Nile. These two rivers were identified with two of the four rivers that, according to the Bible, flowed from Eden: the Thanais and the Ghion, respectively.